Epidemiological profile of animal bite victims attending anti-rabies clinic in a tertiary care hospital in eastern Rajasthan: An observational study - Ankit Raj; Shalini Singh; Dharmesh Sharma; Rajeev Yadav (MGM Journal of Medical Sciences)
Background: India has been classified by the World Health Organization as an endemic country with the highest incidence of rabies-related deaths globally. Therefore, any instance of a dog or wild animal bite is considered a potential exposure to rabies. The National Action Plan for Dog-Mediated Rabies Elimination emphasizes the importance of formulating state and district-level action plans tailored to local circumstances and evidence. A cross-sectional study analyzed the epidemiological traits of animal bites reported at the anti-rabies clinic of a tertiary hospital in Jaipur, Rajasthan, India. Materials and Methods: The research was conducted at Sawai Man Singh Medical Hospital in Jaipur, India, from September to October 2022. A pretested interviewer-administered questionnaire was used to collect data on the socio-demographic and epidemiological features of animal bites from a sample of 328 victims. Descriptive statistics and a spatial map were employed to analyze the results. Results: Among animal bite victims, 73% were males, and 35% fell within the age group of 5–18 years. The majority of cases, accounting for 92%, were categorized as category III exposure, with 61% of the victims being bitten on their lower limbs. Dogs were responsible for 76% of the bites, while monkeys accounted for 21%. Approximately 74% of dog bites were inflicted by stray dogs, and 82% of these incidents were unprovoked. Conclusion: The study highlights a higher prevalence of category III exposure and monkey bites compared to previous research, along with subpar adherence to prior immunizations. Most animal bite incidents were observed in public areas, particularly on streets and tourist destinations. These findings emphasize the importance of customizing district and state action plans to the specific context in Rajasthan to combat rabies effectively.